PERILAKU HYGIENE SANITASI PEDAGANG MAKANAN JAJANAN DAN PERILAKU JAJAN SISWA DENGAN KEJADIAN DIARE DI SEKOLAH DASAR - Julietta br Girsang; Deli Syaputri; Risnawati Tanjung; Yustina Siregar Siagian (Poltekkes Kemenkes Medan, 2023)
ABSTRACT Food sanitation is an effort to secure and save food to keep it clean, and healthy. Hygiene of food handlers is the key to success in food processing that is healthy and safe Children's snack behavior will be influenced by children's knowledge, attitudes, and actions regarding the selection of healthy snacks.The food that is very liked by elementary school aged children is street food. Reflection of childrens habits is In consuming snack that are not good can affect children nutrition. The cleanliness of snacks can affect the incidence of diarrhea due to the use of hazardous substances and can result in food poisoning. This research was a quantitative study with a cross-sectional study design, the sample taken was 10 vendors and 51 student respondents. The sampling technique used was non-probability sampling where the researcher took data using a questionnaire which was filled in directly by the respondent. The results showed that from 10 respondents the sanitation hygiene behavior of street food vendors in 101799 was still said to be not good, because there were found some street food vendors who had poor food sanitation hygiene behavior. Then the results of the bivariate analysis of 51 elementary school students showed that there was a correlation between knowledge of snacking and the incidence of diarrhea (p value 0.000), attitudes to the incidence of diarrhea (p value 0.000), actions with the incidence of diarrhea (p value 0.012).